2014
DOI: 10.1097/wnp.0000000000000034
|View full text |Cite|
|
Sign up to set email alerts
|

Intraoperative Somatosensory Evoked Potential Monitoring Decreases EEG Burst Suppression Ratio During Deep General Anesthesia

Abstract: Data from this study show that somatosensory input can evoke bursts, altering the "spontaneous" deep BS patterns (BSR(Pre) >30%). Further studies are necessary to objectively assess the clinical relevance of stimulus-induced BS reactivity during deep general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The burst suppression represents a very downregulation of cortical activity, where 95% of cortical cells are silent, and therefore mice are deeply unconscious during burst suppression. [ 7,32,33 ] When reaching deep anesthesia, burst suppression continuously occurred. The ratio of EEG theta wave to delta wave power (theta/delta ratio) was calculated, and a simple exponential function was used to fit to the theta/delta ratio y against the time x as ybadbreak=a·eb·x$$\begin{equation}y = a\cdot{e}^{b \cdot x}\end{equation}$$where a and b are two fitting parameters, and parameter b is defined as the anesthesia speed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The burst suppression represents a very downregulation of cortical activity, where 95% of cortical cells are silent, and therefore mice are deeply unconscious during burst suppression. [ 7,32,33 ] When reaching deep anesthesia, burst suppression continuously occurred. The ratio of EEG theta wave to delta wave power (theta/delta ratio) was calculated, and a simple exponential function was used to fit to the theta/delta ratio y against the time x as ybadbreak=a·eb·x$$\begin{equation}y = a\cdot{e}^{b \cdot x}\end{equation}$$where a and b are two fitting parameters, and parameter b is defined as the anesthesia speed.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, some studies reported that the onset of burst suppression on the EEG was used to assess whether the subjects enter the unconscious and deep anesthetic state. [7,32,33] We further analyzed the data of photometry with this criteria. Consistently, we found that the activity of sevoflurane-activated neurons significantly increased during deep anesthetic state compared with baseline.…”
Section: Sevoflurane Activates the Sleep-related Midbrain Neuronsmentioning
confidence: 99%
“…Burst-suppression EEG may also respond to external stimuli. For instance, burst-suppression patterns induced by general anaesthesia can react to peripheral nerve stimulation, auditory or visual stimuli (Calin et al, 2014;Hartikainen et al, 1995). We present two patients with a postanoxic encephalopathy showing burstsuppression patterns with a remarkable response to external stimuli.…”
Section: Introductionmentioning
confidence: 94%
“…Burst-suppression is a characteristic EEG pattern, defined by attenuation or suppression during at least 50% of the recording alternated with high-voltage transients (bursts) with a duration of at least 500 ms and waveforms with at least 4 phases (Hirsch et al, 2013). Burst-suppression can be observed both in physiological conditions, for example during anaesthesia, and in pathological conditions, such as anoxia, intoxication and hypothermia (Amzica, 2009;Iyer et al, 2014;Niedermeyer, 2009;Hartikainen et al, 1995;Chemali et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the times of DEM occurrence reduces the continuous multichannel EEG signal to a single binary time stream marking when the DEM signature is either present (1) or not (0). The DEM reactivity (DER) to photic stimulation (DER PHOT ) could then be calculated (Serban et al, 2022) as the change of occurrence probability during 1 min stimulation as compared with a 1 min stimulation baseline, similar to reactivity measures of the discontinuous burst-suppression EEG (Calin et al, 2014;Nita et al, 2016) that can occur in deep anaesthetic coma (Hartikainen et al, 1995). We found that DER PHOT was decreased as compared with healthy controls in a group of acute post-stroke comatose patients (Serban et al, 2022), a pathology known to be associated with DMN impairments (Dacosta-Aguayo et al, 2015;Ding et al, 2014;Jiang et al, 2018;Tuladhar et al, 2013;Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%